AKTİNİK KERATOZ, BAZAL HÜCRELİ KARSİNOM, SKUAMÖZ HÜCRELİ KARSİNOM VE MALİGN MELANOM 'DA TRPM4 VE TRPM8 REAKTİVİTESİNİN ARAŞTIRILMASI - GÜNEŞ, AZAT (Fırat Üniveristesi, 2024)
Deri kanseri dünya çapında en sık görülen malignitedir. Dünya Sağlık Örgütü, kanser tanısı alan her üç kişiden birinin cilt kanseri olduğunu bildirmiştir. TRPM4 ve TRPM8 iyon kanallarındaki değişiklikler fizyolojik fonksiyonları etkileyerek, patolojik süreçlerin oluşumuna zemin hazırlar. Bu kanallar oksidatif stres ile modüle edilen ve malign hastalıklarda ekspresyonu artan iyon kanallarıdır. Çalışmamız TRPM4 ve TRPM8' in Aktinik Keratoz, Bazal Hücrelİ Karsinom, Skuamöz Hücreli Karsinom, Malign Melanomda immünrektivitesini araştırmayı amaçlamaktadır. Bu çalışma Fırat Üniversitesi Tıp Fakültesi Plastik, Rekonstruktif ve Estetik Cerrahi Kliniğinde Eylül 2019 -Eylül 2023 yılları arasında alınan ve Tıbbi Patoloji Anabilim Dalı tarafından arşivlenen eksizyonel biyopsi örneklerinden yapıldı.. Çalışma dördü hasta biri kontrol grubu olmak üzere 5 gruptan oluşturuldu. Her bir hasta grubundan 15 er hasta toplandı. Çalışmada hem normal cilt hem Aktinik Keratoz, Bazal Hücreli Karsinom, Skuamöz Hücreli Karsinom ve Malign Melanomda farklı histoskorları olsa da TRPM4 ve TRPM 8 'in eksprese edildiği görülmüştür. Ek olarak TRPM-4 için immünreaktivitenin yaygınlık ve şiddeti açısından gruplar arasında anlamlı farklılık görülmüş iken, TRPM-8 için immünreaktivitenin yaygınlık ve şiddeti açısından gruplar arasında anlamlı farklılık görülmemiştir. Çalışmamızın TRPM4 ve TRPM8 in: cilt tümörlerinde prognostik biyobelirteç olarak kullanımı, ekspresyonun tümör boyutlarıyla ilişkisinin değerlendirilmesi, ekspresyonun evreleme ile ilişkisinin değerlendirilmesi gibi yeni çalışmalar için dayanak olabileceğini ön görülebilir. Son olarak özellikle TRPM4' te bizim ulaştığımız anlamlı histoskor farklılığının ve TRPM8 te ise daha önceki çalışmalarda anlamlı farklılık sonuçlarının olması sebebiyle TRPM4 ve TRPM8 anatagonistlerinin cilt tümörü büyümesinin ve ilerlemesinin azaltılmasında pay sahibi olabileceğini ve tümör immünoterapisi için potansiyel hedef olarak hizmet edebileceğini düşünülebilinir. Bu konularda hasta sayılarının fazla olduğu daha ileri çalışmalar yapılabilir.

Skin cancer is the most seen malignency in the world. WHO refers that one third of the all the Cancer diagnosis is skin cancer. The changes within TRPM4 and TRPM 8 ion canals affect physiological functions, thus they give rise to occurrence of patological processes. These canals are the canals which are being modulated by the oxidative stress and are being expressed in the case of malign diseases. Our purpose in this work is the examination of immunreactivity of TRPM4 and TRPM8 within the Actinic Keratosis, Bazal Cell Carsinoma, Squamoz Cell Carsinoma and malignant Melenoma. This study was made upon biopsies that were taken in between Semtember 2019 and September 2023 by the Department of Plastic, Reconstructive and Aesthetic Surgery clinic in the Medicine Faculty of Fırat University. Moreover, these biopsies were archived by the Patology department of Medicine Faculty of Fırat University. This research was made with 4 groups which are comprising of patients and 1 control group in total of 5 groups. From each ilnesses group 15 patients have been taken to these research groups. In the research, although normal skin, actinic keratosis, basal cell carsinoma, squamoz cell carsinoma and malignant melanoma have different histo-scores, TRPM4 and TRPM8 were produced by each of them. Additionaly, in terms of immunreactivity scale and intension, there were a crucial differences between groups about TRPM4, however, the important differences were not detected for the TRPM8 among groups. It can be foreseen that our works are going to be significant database for works about utilization of TRPM4 and TRPM8 as a prognostic biomarker for skin tumors, also works about relation of TRPM4 and TRPM8 production with the size of tumors and its relation with the tumors' stages. Lastly, especially due to the crucial different histo-scores that we have obtained about TRPM4 and the histo-scores those differ from previous works that were made about TRPM8, we claim that TRPM4 and TRPM8 antagonists may have role in the case of decreasing skin tumour growth and progress, also it can be thought that these antagonists can serve as a potential target for tumor immunoteraphy. About these topics, further research can be done and further works that contain more crowded patient groups can be carried out.
Examination of reactivity of trpm4 and trpm8 within actinic keratosis, basal cell carsinoma, squamoz cell carsinoma and malignant melanoma
Keywords: Plastik ve Rekonstrüktif Cerrahi